Kirurško zdravljenje bolnikov z rakom debelega črevesa na Oddelku za abdominalno in splošno kirugijo Splošne bolnišnice Maribor v obdobju 1998 - 2001 - Gajzer, Borut (Zdravniški vestnik, 2004)
Background. The aim of this paper is to present and assess a surgical treatment of patients with colon cancer. Methods. All patients with colon cancer, who were operated in years 1998-2001, were included in the analysis. We have collected data including patients age, localization and stage of cancer, types of preformed procedures, postoperative mortality, disease recurrence and survival of the patients. Results. We have operated on 308 patients with histological evidence of colon cancer in above mentioned period. The average patients age was 66.5 years (SD = 11.1; 95% CI: 44.3-88.7). Primary tumor was most commonly (36%) located in sigmoid colon. UICC stages were as follows: stage I 34 patients, 11%; stage II 141, 46%; stage III 64, 21%; stage IV 69, 22%. We have performed 287 resections of colon (93% resectabillity), of these 214 (75%) were potentially curative R0 resections. Share of urgent procedures was 21%. In the postoperative period 22 patients (7%) have died. Postoperative mortality was significantly higher by urgent (19%) compared to scheduled procedures (4%) (chi sup2 = 16; df = 1; p = 0,005). In the observed time 22% of patients developed recurrent cancer. Mean survival rate of our patients was 1274 days or 3.5 years (SD = 191; 95% CI: 900-1648). Calculated overall five years survival rate was 45%. Conclusions. Planned and registered surgical treatment of patients with colon cancer, surgical specialization in colon surgery and adjuvant oncological treatment have shown the same incentive results, reflected in increased survival rate.
Keywords: Colonic neoplasms; Mortality; Surgical procedures, operative; Survival